Disaster management plan for the Immaculate Conception Academy East Library - Pascua, Rae Clement B.; Olgado, Benedict S. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2015)
Disasters are events that cause damage and destruction to humans and buildings. Libraries face emergencies such as disasters that they need to be ready for all the time. When a disaster occurs, the damages and consequences to human lives are apparent. In addition, library equipment, collections and facilities are at risk especially if the institution is not prepared.
This study focused on creating a disaster management plan for the Immaculate Conception Academy East Library. The data gathered from the surveys, questionnaires, and interviews given to the Immaculate Conception Academy East Library staff revealed that the library does not have a formal written disaster management plan and the top three (3) risks in the library collection were: fire, flood, and infestation while the top risks in the library building were: fire and earthquake. The study also revealed that the awareness and preparedness of the library staff should also be put into consideration.
This study recommends that the Immaculate Conception Academy East Library should have its own formal written disaster management plan. The study also recommends that the institution should continue having its school emergency and disaster preparedness committee and from there, start to create a disaster management plan.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Libraries -- Risk management -- Philippines -- Quezon City; Emergency management -- Philippines -- Quezon City